State vocational rehabilitation programs and federal disability insurance: An analysis of Virginia's vocational rehabilitation program - David Dean; John V. Pepper; Robert M. Schmidt; Steven Stern (IZA Journal of Labor Policy, 2014)
We examine the association between the receipt of vocational rehabilitation (VR) services and Federal Disability Insurance using a unique panel data source on persons who applied for assistance from Virginia's VR program in 2000. Three central findings emerge: first, VR services are associated with lower rates of participation in disability insurance programs-a nearly 2 point drop in SSDI receipt and 1 point drop in SSI receipt. Second, VR service receipt is associated with lower take-up rates of SSDI/SSI. Finally, among VR applicants on SSDI/SSI, those who receive substantive VR services are more likely to be employed.
Keywords: H51; I13; J24; 330; Vocational rehabilitation; Disability insurance